HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SISWA DI SDN 010 BERINGIN JAYA SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Tohirin, Tohirin; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on the observation that the author did in SDN 010 Beringin Jaya Sentajo Raya Regency Kuantan Singingi, there are still many students who are learning outcomes is low. It is seen and be based on learning outcomes for students penjasorkes even semester 2016 listed in report students. Low penjasorkes student learning outcomes is probably due to the nutritional status of students, therefore the purpose of this study was to determine the relationship of nutritional status and the student learning outcomes SDN 010 Beringin Jaya. This type of research is correlational while samples were students of class V SDN 010 Beringin Jaya amounting to 22 with a total sampling technique. Data obtained from measurements of height and weight of the sample fatherly nutritional status and value of MID semester for student learning outcomes. Data analysis using product moment correlation and Liliefors test for normality. Having analyzed the data obtained rhitung 0,495 rtabel 0.433, meaning that there is a relationship of nutritional status to learning outcomes penjasorkes students at SDN 010 Beringin Jaya Sentajo Raya. In other words, the hypothesis was accepted.Keywords : Nutrition Status, Learning Outcome